THE VISUAL APPEAL OF ACTORS IN GENERATION Z’S PERCEPTION OF MOTIVATIONS FOR WATCHING KOREAN DRAMAS - Mikael Dito Bangun Napitupulu; RR. Roosita Cindrakasih (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2026)
The development of digital media has driven the increasing consumption of Korean dramas among Generation Z in Indonesia through internet-based streaming platforms that are increasingly accessible to society. One aspect that plays a role in viewing decisions is the visual appeal of actors, encompassing physical appearance, style of dress, facial expressions, and aesthetic impressions displayed in Korean dramas. This study aims to understand Generation Z's perception of the visual appeal of Korean drama actors, identify viewing motives, and describe the meaning of actors' visual appeal in relation to those motives. The study was conducted at Jl. Cempaka VI, RT 008/RW 09, Kelurahan Cakung Timur, Kecamatan Cakung, East Jakarta. The method used was descriptive qualitative, with data collection through observation, in-depth interviews, and documentation involving three Generation Z informants and one expert triangulator in Communication Studies. The findings indicate that the visual appeal of actors serves as a first impression triggering viewer interest in Korean dramas. Viewing motives include entertainment, visual satisfaction, emotional closeness with characters, and the desire to follow South Korean popular culture trends. Thus, the visual appeal of actors is interpreted as an important element in viewing motives among Generation Z in Cempaka VI, Cakung Timur